Activation of TAF9 via Danshensu-Induced Upregulation of HDAC1 Expression Alleviates Non-alcoholic Fatty Liver Disease - Wang, Ruiwen; Wang, Zhecheng; Sun, Ruimin; Fu, Rong; Sun, Yu; Zhu, Meiyang; Geng, Yunfei; Gao, Dongyan; Tian, Xiaofeng; Zhao, Yan; Yao, Jihong (Frontiers in Pharmacology, 2021)
Fatty acid β-oxidation is a key pathogenic mechanism underlying nonalcoholic fatty liver disease (NAFLD), and TATA-box binding protein associated factor 9 (TAF9) has been reported to be involved in the regulation of fatty acid β-oxidation. However, the function of TAF9 in NAFLD, as well as the mechanism by which TAF9 is modulated, remains unknown. In this study, we aimed to investigate the signaling mechanism underlying the involvement of TAF9 in NAFLD and the protective effect of the natural phenolic compound Danshensu (DSS) against NAFLD via the HDAC1/TAF9 pathway. An in vivo model of high-fat diet (HFD)-induced NAFLD and a palmitic acid (PA)-treated AML-12 cell model were developed. Pharmacological treatment with DSS significantly increased fatty acid β-oxidation and reduced lipid droplet (LD) accumulation in NAFLD. TAF9 overexpression had the same effects on these processes both in vivo and in vitro. Interestingly, the protective effect of DSS was markedly blocked by TAF9 knockdown. Mechanistically, TAF9 was shown to be deacetylated by HDAC1, which regulates the capacity of TAF9 to mediate fatty acid β-oxidation and LD accumulation during NAFLD. In conclusion, TAF9 is a key regulator in the treatment of NAFLD that acts by increasing fatty acid β-oxidation and reducing LD accumulation, and DSS confers protection against NAFLD through the HDAC1/TAF9 pathway.